Multiple‐microarray analysis for identification of hub genes involved in tubulointerstial injury in diabetic nephropathy. Issue 9 (13th February 2019) - Zeng, Mengru; Liu, Jialu; Yang, Wenxia; Zhang, Shumin; Liu, Fuyou; Dong, Zheng; Peng, Youming; Sun, Lin; Xiao, Li
Abstract: Diabetic nephropathy (DN) is a primary cause of renal failure. However, studies providing renal gene expression profiles of diabetic tubulointerstitial injury are scarce and its molecular mechanisms still await clarification. To identify vital genes involved in the diabetic tubulointerstitial injury, three microarray data sets from gene expression omnibus (GEO) were downloaded. A total of 127 differentially expressed genes (DEGs) were identified by limma package. Gene set enrichment analysis (GSEA) plots showed that sister chromatid cohesion was the most significant enriched gene set positively correlated with the DN group while retinoid X receptor binding was the most significant enriched gene set positively correlated with the control group. Enriched Gene Ontology (GO) annotations and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways of DEGs mostly included extracellular matrix organization, extracellular space, extracellular matrix structural constituent, and Staphylococcus aureus infection. Twenty hub genes from three significant modules were ascertained by Cytoscape. Correlation analysis and subgroup analysis between hub genes and clinical features of DN showed that ALB, ANXA1, APOH, C3, CCL19, COL1A2, COL3A1, COL4A1, COL6A3, CXCL6, DCN, EGF, HRG, KNG1, LUM, SERPINA3, SPARC, SRGN, and TIMP1 may involve in diabetic tubulointerstitial injury. ConnectivityMap analysis indicated the most significant three compounds are 5182598, thapsigargin and 5224221. In conclusion, this study may provide new insights into the molecular mechanisms underlying diabetic tubulointerstitial injury as well as potential targets for diagnosis and therapeutics of DN. Abstract : In conclusion, the present study aimed to identify key molecules involved in diabetic tubulointerstitial injury. One hundred and twenty‐seven differentially expressed genes (DEGs) and 20 hub genes were screened via this multiple‐microarray analysis, which may become potential targets for future diagnosis and treatment of diabetic nephropathy (DN).